2008
DOI: 10.1540/jsmr.44.217
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of Psidium guajava Linn. (Myrtaceae) leaf aqueous extract on rat isolated vascular smooth muscles

Abstract: In this study, we examined the effects of Psidium guajava Linn. leaf aqueous extract (PGE) on isolated, spontaneously-contracting portal veins, as well as on endotheliumintact and endothelium-denuded descending thoracic aortic ring preparations of healthy, normotensive rats. Graded concentrations of PGE (0.25-4.0 mg/ml) caused concentration-dependent, initial brief but significant (P<0.05) rises of the basal tones and amplitudes of pendular, rhythmic contractions, followed by secondary pronounced, longer-lasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Biphasic effect has been identified in other studies with herbal products that evaluated vasodilator activity of natural substances extracted from plants. Regarding this effect, the authors mentioned that it was due to a transient increase in Ca 2+ influx from the extracellular medium (Chiwororo & Ojewole, 2008;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic effect has been identified in other studies with herbal products that evaluated vasodilator activity of natural substances extracted from plants. Regarding this effect, the authors mentioned that it was due to a transient increase in Ca 2+ influx from the extracellular medium (Chiwororo & Ojewole, 2008;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The work concluded that the activity may be related to rosmarinic acid, eugenol, carvacrol, catechin, and caffeic acid since they were the major constituents of their extracts. In addition, this activity was supported by the biphasic and contractile effect on rat vascular smooth muscles [119,120]. …”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…In that study, the vasodilatory effect exerted On the other hand, successive doses of PRL precipitated a biphasic effect. It has been reported that different molecules [59,60] including hormones [61] , exert dual effects comparable with the effects exerted by PRL; for example, angiotensin II causes transient coronary constriction and exerts positive inotropic effects in some cardiovascular models [62,63] as a result of either progressive endothelial angiotensin I receptor internalization or receptor desensitization [64] , effects associated with tachyphylaxis. In our study, both the effects of the successive doses of PRL and the decreased vasodilation induced by the first PRL dose may be related to an endothelial desensitization process, as cumulative doses of PRL did not exert direct effects on aortic smooth muscle.…”
Section: Discussionmentioning
confidence: 99%